Relationship between everolimus exposure and safety and efficacy: Meta-analysis of clinical trials in oncology - Ravaud, Alain; Urva, Shweta R.; Grosch, Kai; Cheung, Wing K.; Anak, Oezlem; Sellami, Dalila B. (European journal of cancer (1990), 2014)
In patients with solid tumours, daily everolimus dosing demonstrated dose proportionality and linear pharmacokinetics. A meta-analysis was conducted to characterise the relationship between everolimus Cmin and efficacy and safety and the effect of CYP3A4 and P-glycoprotein (PgP) substrate/inhibitor/inducer coadministration on everolimus trough concentration (Cmin). Individual patient data from five phase 2/3 studies, in which steady state, predose pharmacokinetic samples were taken from patients with solid tumours administered everolimus 10mg/day, were pooled. Efficacy and safety were evaluable for 945 and 938 patients, respectively. A 2-fold increase in everolimus Cmin increased the likelihood of tumour size reduction (odds ratio 1.40, 95% confidence interval (CI) 1.23–1.60), was associated with a trend for reduced risk of progression-free survival events (risk ratio [RR] 0.90, 95% CI 0.69–1.18) and increased the risk of grade ⩾3 pulmonary (RR 1.93, 95% CI 1.12–3.34), stomatitis (RR 1.49, 95% CI 1.05–2.10) and metabolic (RR 1.30, 95% CI 1.02–1.65) events. Coadministering everolimus with strong CYP3A4 and PgP inhibitors increased everolimus Cmin by 10% and 20%, respectively; coadministration with CYP3A4 inducers reduced Cmin by 7%. A 2-fold increase in everolimus Cmin was associated with improved tumour size reduction and increased risk of high-grade pulmonary, metabolic and stomatitis events. Novartis Pharmaceuticals Corporation.